Recurrent Massive Hemoptysis due to Postbronchotomy Bronchial Artery Aneurysm: A Case Report - Achilleas Lioulias; Panagiotis Misthos; John Kokotsakis; Georgios Papagiannakis; Elian Skouteli (Canadian Respiratory Journal)
Bronchial artery aneurysm (BAA) is a rare clinical entity. A case of intrapulmonary BAA associated with previous bronchotomy at the same site is described. A 22-year-old woman, who had undergone bronchotomy of the intermediate bronchus for the removal of a foreign body four years previously, presented with recurrent hemoptysis. Because of an increased risk for spinal cord ischemia, she immediately underwent lung resection rather than therapeutic embolization. The incidental finding of a BAA of any cause cannot be assumed to be stable, and immediate management should be undertaken regardless of the presence or absence of symptoms.